RELATIONSHIP BETWEEN LEARNING DISCIPLINE, PEER FRIENDS AND ATTENTION OF OLD PEOPLE WITH MATHEMATICS STUDENT LEARNING OUTCOMES IN SMA NEGERI 3 BANTUL - Sefrilina Hastutiningsih; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2017)
A minimum outcome is related to many factors. The discipline of learning, peers, and parent’s attention are some of the factors that were related to learning outcomes. This study aims to determine the presence or absence of a positive and significant relationship between the disciplines of learning, peers and parents' attention to learnings outcomes math class X Semester SMA Negeri 3 Bantul academic year 2015/2016. The population of this the research second-semester students of class X SMA Negeri 3 Bantul Academic Year 2015/2016 consists of 7 classes. The research sample by random sampling technique then got X 6 as the sample of the research and X 5 as a trial class. The techniques of data collection was conducted by questionnaire and test methods. Test instruments used validity, reliability test and test different power. The prerequisite analysis test including normality test, linearity test, and the independence test. The data are collected the researcher uses product-moment and multiple linear regression analysis to analyze the data. The results of the data shows that there is a positive and significant correlation between learning discipline, peers and parents attention to the results of learning mathematics, with 6,2987 and 3,03, in order to, obtain . The coefficients multiple correlation (R) of 0,6716 with a linear regression equation -115,1360 + 0,8845 X1 + 0,8508 X2 + 0,2196 X3. The contribution large relative (X1) = 53.0585%, (X2) = 31.8447%, (X3) = 15.0968% with double the coefficient of determination of of 0.510 as well as the effective contribution (X1) , (X2) = 14.3627%, (X3) = 6.8090%.